3D SAR (SYNTHETIC APERTURE RADAR) IMAGING SIMULATION USING JAVA - Erfansyah Ali; Andriyan B Suksmono (TEKTRIKA, 2016)
One of methods in remote sensing is Synthetic Aperture Radar (SAR). When combined with Range DopplerAlgorithm (RDA) can produce smaller radar resolution only by using normal sized antenna placed atplatform. RDA is able to generate much wider aperture â€œsyntheticâ€ antenna, resulting very narrow beamwidthwhen reach earth's ground. By using already established 2D SAR methods in accuracy andprocessing speed this 3D SAR simulation was developed. Simulated on 15 x 15 pixels grayscale targets atdifferent heights, 3D SAR developed on this research can detect object's height accurately. Thissimulation was developed using JAVA as steppingstone in implementing SAR image processing in smallsystem like embedded system or micro computing which normally using C programming language.